Accuracy of Ultrasound for Preoperative Assessment of Tumor Size in Patients With Newly Diagnosed Breast Cancer: Is It Affected by the Background Parenchymal Echotexture?. (17th April 2018) - Ko, Kyung Hee; Son, Eun Ju; Kim, In Wha
Abstract : Objectives: To assess the impact of the background parenchymal echotexture on the accuracy of tumor size estimation using breast ultrasound (US). Methods: A total of 140 women with newly diagnosed invasive breast cancer from January 2014 to December 2015 were enrolled in this study. Two radiologists retrospectively reviewed US images in consensus for background parenchymal echotexture interpretation. The maximum tumor diameter from static images was recorded. Tumor size measurements were considered as having agreement with histologic results if they were within ±5 mm compared to the pathologic size. The relationship between the accuracy of tumor size measurement by the background parenchymal echotexture and clinicopathologic characteristics was evaluated. Results: Of these 140 patients, 77 (55.0%) showed a homogeneous background parenchymal echotexture, whereas 63 (45.0%) showed a heterogeneous echotexture. The mean tumor size was 1.9 cm (range, 0.5–4.9 cm). The overall accuracy of tumor size measurement was 76.4% (104 of 140). Tumors of women with a homogeneous background parenchymal echotexture were more accurately measured than those of women with a heterogeneous echotexture (87.0% versus 63.5%; P = .001). Tumors with a small size (<2 cm; P = .018) and ductal carcinoma in situ–negative ( P = .031), human epidermal growth factor receptor 2 (HER2)‐negative ( P = .053), and triple‐negative ( P = .016) types were also more accurately measured. The independent factors associated with inaccurate tumor size measurement were a heterogeneous background parenchymal echotexture, a large tumor size, and the HER2‐enriched type ( P < .05). Conclusions: The background parenchymal echotexture affected the accuracy of tumor size estimation using breast US. Invasive breast cancers with large (≥2 cm) tumors and the HER2‐enriched type showed significantly lower breast US accuracy compared to others.